Enhancing Machinability of Hardfaced JIS-FC25 Gray Cast Iron: Coolant Application and Its Trade-offs - Mookam, Niwat; Pongsa, Uraiwan; Jaemsang, Orajit; Madsa, Tavee (Journal of Advanced Development in Engineering and Science, 2026)
This study aimed to investigate the machinability of hard-faced layers on JIS-FC25 gray cast iron, which were deposited in three layers using the shielded metal arc welding (SMAW) process. The experiments were conducted under two conditions: dry milling and wet milling using a coolant composed of oil and water in a 1:20 ratio. The milling parameters were kept constant with a cutting depth of 1 mm, spindle speed of 800 rpm, and feed rate of 100 mm/min. The experimental analysis focused on chip morphology, tool wear (flank wear), and the surface roughness of both the cutting edge and the machined workpiece. The results indicated that coolant application improved chip length and consistency, reduced friction, and enhanced lubrication during the milling process. However, in long-distance milling operations, wet milling led to accelerated tool degradation due to thermal cycling effects. In contrast, dry milling exhibited more stable tool wear and lower surface roughness over extended cutting distances. The findings suggest that dry milling is more suitable for long cutting operations as it minimizes tool wear and maintains better surface quality.Therefore, the selection of milling conditions should be tailored to match the specific requirements of real-world applications.